A new concept: 'Relative position between the external force and the bony prominence' explains location-specific occurrence of superficial injury over an undermining lesion. Issue 1 (February 2017) - Takahashi, Yoshiko; Nemoto, Tetsuya; Mizokami, Fumihiro; Furuta, Katsunori; Murasawa, Yusuke; Yoneda, Masahiko; Isogai, Zenzo
Abstract: Aim: A pressure ulcer is localized injury to the skin and/or underlying tissue usually over a bony prominence, as a result of pressure, or pressure in combination with shear. Although the external forces and bony prominences differ depending on ulcer location, the way in which these anatomical differences affect pressure ulcer development is not well studied. Methods: To clarify the location-dependent factors for pressure ulcer development, we focused on superficial injuries that develop over an undermining lesion, which we have termed them bilayer pressure ulcers. Because it is thought that a deep pressure ulcer is caused by ischemia at the deep lesion and a shallow pressure ulcer is caused by shear force to the superficial skin, a bilayer pressure ulcer can be considered a mixed phenotype, induced by both pressure and shear force. We retrospectively examined the frequency of bilayer pressure ulcers by location in a total of 568 pressure ulcers. Results: The ratio of bilayer pressure ulcers to deep pressure ulcers staged III or more was significantly larger for pressure ulcers over the sacrum. Conclusion: A new concept, the relative position between the external force and bony prominence, could explain the frequency and developmental mechanism of bilayer pressure ulcers. The external forces, shape of the bony prominence, and mobility of the soft tissue may be responsible for this concept. Highlights: Superficial injuries that developed over an undermining lesion of pressure ulcers were examined. This type of pressure ulcer was termed a bilayer pressure ulcer. A bilayer pressure ulcer is induced by both pressure and shear force. Bilayer pressure ulcers were more frequent among pressure ulcers over the sacrum. Relative position between the external force and bone is critical for development.